Assessment of Current Situation of Aquaculture Pollution in Tianjin and Its Prevention and Control Measures. Issue 1 (June 2021) - Liu, Jiahong; Wei, Daiyan; Yang, Jidong; Yi, Xiaojuan; Sun, Meng
Abstract: In order to grasp the current situation of aquaculture pollution in Tianjin, the situation of Tianjin aquaculture and the characteristics of tail water discharge were studied. The results showed that Tianjin's aquaculture area in 2019 was 398, 000 mu, of which 384, 000 mu was freshwater aquaculture; the tail water discharge was 448 million cubic meters, of which freshwater aquaculture emissions were 384 million cubic meters; the main pollution factor for freshwater aquaculture was chemical oxygen demand ( CODCr ) and total phosphorus, chemical oxygen demand ( CODCr ) all exceed the standard, the total phosphorus compliance rate is 18.8%, ammonia nitrogen and total nitrogen are both up to the standard; the main pollution factors of pond aquaculture in marine aquaculture are chemical oxygen demand ( CODCr ) and reactive phosphate and total phosphorus. The main pollution factors of factory-aquaculture are inorganic nitrogen, reactive phosphate and total nitrogen. The concentration of inorganic nitrogen, reactive phosphate, total nitrogen and total phosphorus in factory-aquaculture using circulating water is higher than that using non-circulating water; Tianjin's annual aquaculture chemical oxygen demand discharges 32, 700 t, ammonia nitrogen 348.0 t, total phosphorus 367.3 t, and total nitrogen 2025.6 t; countermeasures and suggestions are put forward for the pollution of aquaculture.